Delineation of functional determinants in the transforming protein of Fujinami sarcoma virus. - Johnson, K A (1990)
We analyzed linker insertion mutations throughout the 3' region of the v-fps gene of Fujinami sarcoma virus to identify tyrosine kinase transforming protein (P130gag-fps) determinants that are important for catalysis and transforming activity and, in particular, to define residues that participate in substrate selection. Mutations that encode kinase-active, transformation-defective v-fps alleles were recovered, defining sites in the transforming protein that may normally facilitate kinase-substrate interaction. Additionally, one region within the catalytic domain of the transforming protein (amino acid residues 1012 to 1020) that tolerates peptide insertions without loss of transforming activity was discovered, although the insertion mutations in this region of v-fps exhibited qualitatively abnormal transforming function. Transformed rat cell lines that express these mutations displayed unusual phenotypes, including giant cells and cells with an extremely fusiform shape. Furthermore, the insertion mutations in this region were temperature sensitive, transformed cells assumed a flat morphology, cellular protein phosphotyrosine was reduced, and the kinase activity of the transforming protein was decreased when cells were incubated at 40.5 degrees C. Point mutations that specify the ancestral chicken c-fps sequence in the insertion-tolerant region were also introduced into v-fps. These back mutations led to a modest decrease in kinase activity, decreased tumorigenic potential in chickens, and an unexpected increase in transforming activity in rat cells. These results indicate that the insertion-tolerant region of P130gag-fps influences the biologic activity and thermostability of the kinase.